Antimalarial activity of isoquine against Kenyan Plasmodium falciparum clinical isolates and association with polymorphisms in pfcrt and pfmdr1 genes - Okombo, John; Kiara, Steven M.; Abdirahman, Abdi; Mwai, Leah; Ohuma, Eric; Borrmann, Steffen; Nzila, Alexis; Ward, Steve (The journal of antimicrobial chemotherapy, 2013)
The use of amodiaquine in prophylaxis is associated with serious toxicity, resulting from its metabolic conversion into a reactive quinone-imine metabolite by the hepatic cytochrome P450. To circumvent this toxicity, several amodiaquine analogues that lack the potential to form a quinone-imine derivative, while retaining antimalarial activity, have been designed. Isoquine is one of these promising molecules that has already reached Phase I clinical trials in humans.We analysed the in vitro activity of isoquine against 62 Plasmodium falciparum isolates collected in Kenya and the association of this activity with polymorphisms in pfcrt and pfmdr1 genes.The median concentration of isoquine that inhibited 50% of parasite growth (IC50) was 9 nM, compared with 56 nM chloroquine, 8 nM amodiaquine, 10 nM desethylamodiaquine, 69 nM lumefantrine and 1 nM dihydroartemisinin. Isoquine activity was correlated with polymorphisms in pfcrt at codon 76, but not in pfmdr1 at codon 86.The high activity of isoquine against field isolates, including chloroquine-resistant isolates, with IC50 <10 nM, warrants its further development as an antimalarial.
Advance access publication 20 November 2012
Gesehen am 06.12.2021